The symphony concert in Nazi Germany - Gregor, Neil (The University of Chicago Press, 2025)
"A new history of how the musical worlds of German towns and cities were transformed during the Nazi era. In the years after the Nazis came to power in January 1933 and through the war years all aspects of life in Germany changed. However, despite the social and political upheaval, gentile citizens were able to continue leisure activities such as attending concerts. In this book, historian Neil Gregor surveys the classical concert scene in Nazi Germany from the perspective of the audience, rather than institutions or performers. Gregor delves into the cultural lives of ordinary Germans under conditions of dictatorship. Did the ways in which Germans heard music in the period change? Did a Nazi way of listening emerge? For audiences, Gregor shows, changes to the concert experience were small and often took place around the edges. This, combined with the preserved idea of the concert hall as a space of imagined civility and cultivation, led many concertgoers and music lovers to claim after the war that their field and their practice had been innocent-a place to retreat from the vicious violence and racism of the Nazi regime. Drawing on untapped archival sources, The Symphony Concert in Nazi Germany reveals that the true history was one of disruption but also of near effortless adaptation. Through countless small acts, the symphony concert was reframed within the languages of strident nationalism, racism, and militarism to ensure its place inside the cultural cosmos of National Socialist Germany"--